Environmental Resource - Economized Processes of Recycling Mineral Raw Materials of Complex Composition (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The results of the studies on the justification of technological processes providing recycling of the warehoused ferruginous quartzites of complex composition and waste non-ferrous metals allowing to receive additional commodity products are given. The example of amphibole and biotite varieties of ferruginous quartzites of CMA and tailings of copper-zinc sulphide Ural ores determines the reasons of ineffective use of traditional technology solutions for recycling. The reasons of environmental hazards concerning varieties of technogenic mineral substances to the environment are identified. The presence in ferruginous quartzites complex composition of various silicates, carbonates and iron sulphides change their technological properties. So to get the iron concentrate from them suggests a new combination of technological operations performed in specially selected operating conditions. The specifics of the presence of mineral components in solid mineral wastes of nonferrous metal ores indicates the possibility of obtaining additional marketable products. With the use of laboratory multiscale modelling and physical methods of analysis regularities of variation of fractionation, separation and mineral concentration operations efficiency by varying its composition and the various influencing factors are identified. To improve the efficiency of the individual technological operations it is recommended to use different techniques, using physical and physico-chemical effects on the polymineral systems. The flow diagrams for the considered varieties of technogenic processing of mineral substances, allowing them to obtain standared quality products (metal-containing concentrates), and the results of their testing are submitted. The suggested technological solutions can reduce the amount of environmentally hazardous mineral substance, hosted in technogenic formations.